Development of Discovery Learning Based Modules in Ecosystem Material for Class X Senior High School/Madrasah Aliyah Students - Miftahul Jannah Tanjung; Indayana Febriani Tanjung; Miza Nina Adlini (UNDIKMA, 2023)
This study aims to develop Discovery Learning Based Modules and to determine the level of feasibility, practicality and effectiveness of the developed modules. This study uses the Research and Development (R&D) research method with the ADDIE model consisting of five stages, namely (Analysis, Design, Development, Implementation, Evaluation). The research subjects were class X MIPA at SMA Negeri 4 Binjai with a total of 25 students. The research instruments were teacher needs analysis, validation sheets to obtain product feasibility data, educator response questionnaires and student questionnaires to obtain product practicality data and learning achievement tests to obtain data on the effectiveness of the products being developed. Based on the results of the study in terms of feasibility, material experts scored 94.28% in the